152 EXPLORATORY ANALYSIS OF TROPONIN AS BIOMARKER OF ACUTE ISCHAEMIC STROKE SUBTYPES IN A GROUP OF PATIENTS RECRUITED TO THE MIND STUDY. (25th October 2022) - Bejleri, J; Cvetkova, J; Williams, D; Pfeiffer, S
Abstract: Background: Stroke is a major common cause of acquired disability and death worldwide. Atrial dysfunction or cardiomyopathy, defined by the presence of specific serum biomarkers, ECG findings, or echocardiographic findings, increases the risk of atrial fibrillation, which has been implicated as a key risk factor for ischaemic stroke. There is now growing body of evidence which suggests that early positive troponin after ischaemic stroke may be independently associated with a cardiac embolic source. miRNA as Novel Diagnostic biomarker (MiND) is a current Irish-led research study whose aim is to discover a unique highly diagnostic and prognostic biomarker expressed in acute ischaemic stroke. Methods: Data were retrospectively extracted from patients recruited to the MiND study with confirmed diagnosis of acute ischaemic stroke within 12 hours of symptoms onset having also undergone high-sensitivity troponin testing from July 2019 to November 2021. Stroke subtypes were classified as per ESUS criteria. Statistical analysis was carried out using STATA/SE, version 16.0. Results: We identified 52 patients who had troponin performed within 12 hours of symptoms onset. Twenty-two patients were identified as having cardioembolic stroke (CE), 17 as non-cardioembolic stroke (NCE) and 13 as Embolic stroke of unknown source (ESUS). The mean age for each group was 77.5 (±9.8), 65.5 (±12.8) and 66.3 (±11.7) years, respectively. The rate of troponin positivity for each group was 55% (12/22), 29% (5/17) and 15% (2/13), respectively. The unadjusted logistic analysis revealed a positive association between CE stroke subtype and elevated troponin (OR 3.94, 95% 1.20-12.98, p = 0.024) and an inverse association between ESUS stroke subtype and elevated troponin (OR 0.24, 95% CI 0.05-1.21, p = 0.083). Conclusion: Our analysis reveals that early positive troponin after ischaemic stroke is a strong predictor of CE stroke subtype but not of ESUS stroke subtype.